Enzyme modulation and antimicrobial activity of the polyhydroquinoline derivative 4-(4-hydroxy-phenyl)-2-methyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylic acid ethyl ester (Revista Brasileira Multidisciplinar, 2026)
N-heterocyclic compounds are widely used in medicine and pharmacology due to their enormous diversity of biological activities (for example: antimicrobial, anticonvulsant, anti-inflammatory, anticancer, anthelmintic, antihistamine, antihypertensive, and antidepressant). Thus, these compounds are relevant for the synthesis of new drugs. The molecule 4-(4-Hydroxy-phenyl)-2-methyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylic acid ethyl ester was obtained using a multicomponent reaction. Its biological prospection included modulating action on phospholipases A2 and proteases, assessment of cytotoxicity and effects on processes associated with hemostasis, and antimicrobial activity. Several doses of the molecule were tested in each test, ranging from 25 to 500 mg. For antimicrobial activity, in the serial dilution test, the molecule exerted significant inhibitions for both S. aureus and P. aeruginosa. When assessed the effects on the coagulation of citrated human plasma, the molecule previously incubated with Bothrops moojeni venom (40 µg) was able to delay plasma coagulation, induced by proteases, in 14 and 13.66 seconds (p